Que lutas cabem no cais? um olhar através das experiências de mulheres no movimento Ocupe Estelita em Recife – PE - Cavalcanti, Maria Joaquina da Silva (2021)
This dissertation work has as its object the role of women in the struggle for rights within the Movimento Ocupe Estelita, in Recife, Pernambuco, within the theme of gender and the right to the city. It is questioned here what the experiences of women in political mobilization in the struggle within the Ocupe Estelita Movement can say about the way in which social inequalities are placed in the city? To answer the question, the research was carried out with inspiration in the dialectical historical materialist method, as it was undertaken in an analysis considering the contradictions of the reality of women's lives within a historical totality of which their struggle is always a part, prioritizing their reality in the work produced here. The main research corpus of the work consisted of semi-structured interviews with six women who participated in the Ocupe Estelita Movement from 2012 to 2019. The qualitative (RICHARDSON, 2012) and exploratory (GIL, 2008) research methods were used as well as the research technique of unstructured interviews (LAKATOS AND MARCONI, 2003; RICHARDSON, 2012). The general objective of this research is to analyze the experiences of women who participated in the Ocupe Estelita Movement to understand how social relations of gender, race, class and territory are expressed in the city. For this, we seek to reflect on the city model that predominates in Recife and the relationship between the State and the city's real estate capital, and the way in which the law is presented in this case. It is also analyzed how the relations of gender, race, class and territory are shown in the lives of women in the city and also within the Ocupe Estelita Movement itself. The theoretical frameworks used in this research are from studies on urbanism, the right to the city, intersections of race, class and gender, as well as the role of law in these conflicts. Thus, the works of Anne McClintock (2010), Angela Davis (2016), Lefebvre (2001), Harvey (2014), Pachukanis (2017), among others, were used.